Poverty measurement by phone: Developing and testing alternative poverty metrics from the nationally representative Myanmar Household Welfare Survey (MHWS), Round 1 (December 2021-January 2022) - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
Poverty measurement in low and middle income countries (LMICs) has always been challenging, especially among rural households whose incomes are characterized by seasonality, informality and some degree of subsistence consumption. During the COVID-19 pandemic poverty measurement became even more challenging as research had to resort phone surveys, who necessary brevity precludes the use of detailed household expenditure modules preferred in rural settings. Phone surveys instead typically resorted to qualitative questions on income losses and other welfare impacts of economic shocks. Here we use the new nationally representative Myanmar Household Welfare Survey (MHWS) to experiment with three kinds of poverty measures: (1) Asset poverty (10 questions); (2) Income poverty (a maximum of 17 questions); and (3) Food expenditure poverty (based on 4 questions). We first describe the methods for constructing these three indicators – including the poverty lines used for income and food poverty – and their conceptual strengths and weaknesses, before turning to a descriptive analysis of their geographical patterns, their associations with each other and with expenditure-based poverty in the last national survey in 2017. We then test their ability to predict poor diet quality and experiences of hunger, which – based on previous studies – are outcomes that ought to be highly sensitive to household poverty. We draw three important conclusions for measuring poverty in phone surveys. First, asset poverty and income poverty are strongly associated with each other, and with state/region poverty patterns of expenditure-based poverty in 2017. Second, asset poverty was consistently the strongest predictor of poor diet diversity among adults and children, as well as food insecurity at the household level, but income poverty also predicted these outcomes even after controlling for asset poverty. Third, we argue that phone surveys should measure both asset and income poverty, but should likely steer clear of food expenditure measures, which will either require overly long survey instruments, or very short questionnaires susceptible to underestimate of expenditure and overestimation of poverty. However, asset and income poverty are relatively quick and easy to measure, and conceptual complements to each other: income poverty is likely to be sensitive to shocks and seasonality, while asset poverty is insensitive to these fluctuations but captures long-term wealth. Finally, another important benefit of measuring income poverty is its ability to capture the effects of inflationary shocks, as inflation can affect both nominal incomes (e.g. through unemployment) as well as through the analyst’s price adjustments to the real food poverty line.